9-(7-Fluoro-4-oxo-4H-chromen-3-yl)-3,3,6,6-tetramethyl-2,3,4,5,6,7,8,9-octahydro-1H-xanthene-1,8-dione - Mohammad Asad; Chuan-Wei Oo; Hasnah Osman; Hoong-Kun Fun; Suhana Arshad (Acta Crystallographica Section E, 2012)
In the title compound, C26H25FO5, the terminal cyclohexane rings of the xanthene ring system adopt half-boat conformations. The 4H-chromene ring make a dihedral angle of 87.94 (5)° with the xanthene ring system and its carbonyl O atom lies above the xanthene O atom. In the crystal, molecules are linked into ribbons propagating along the a-axis direction by C—H...O hydrogen bonds. Aromatic π–π stacking interactions [centroid–centroid distance = 3.7367 (12) Å] also occur.